Frequent object dropping in carpal tunnel syndrome: a consequence of impaired sensorimotor integration? - MATUR Z.; Dörtcan N.; İmişçi S.; Süner M.; Acar Z.; Sözer N.; Öge A. E. (My University, 2025)
Frequent object dropping is a common complaint in patients with carpal tunnel syndrome (CTS), suggesting potential disruptions in sensorimotor integration. This study investigated the electrophysiological characteristics of sensorimotor integration in CTS patients with and without this symptom. We enrolled twelve CTS patients with frequent object dropping (dCTS), ten CTS patients without noticeable clumsiness (ndCTS), and sixteen healthy controls. All participants underwent clinical evaluation, the Boston Carpal Tunnel Questionnaire, and the Purdue Pegboard Test. To assess sensorimotor integration, electrical stimulation was applied to the median and ulnar nerves, followed by transcranial magnetic stimulation over the contralateral motor cortex at interstimulus intervals (ISIs) of 20, 35, 50, 65, 80, 100, and 200 ms. Motor-evoked potentials (MEPs) were recorded from the thenar and hypothenar muscles. Key findings revealed distinct sensorimotor integration patterns on the dominant side. In the dCTS group, median nerve stimulation at a 35 ms ISI resulted in significantly higher MEP amplitude ratios in the thenar muscles compared to controls. Conversely, in the ndCTS group, ulnar nerve stimulation at ISIs of 20, 80, and 100 ms produced greater MEP ratios in the same muscles. These results demonstrate topographically divergent cortical sensory processing between dCTS and ndCTS patients. One interpretation of these findings is that altered sensorimotor integration from the median nerve underlies the clumsiness in dCTS, while patients without this symptom (ndCTS) may successfully compensate by utilizing sensory input from the ulnar nerve.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Mikrobiyal Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Neurology; Life Sciences; Molecular Biology and Genetics; Microbial Genetics; Health Sciences; Natural Sciences; Klinik Tıp (Med); Yaşam Bilimleri (Life); Klinik Tıp; Sinirbilim ve Davranış; Klinik Nöroloji; Sinir Bilimi; Gelişimsel Biyoloji; Clinical Medicine (Med); Life Sciences (Life); Clinical Medicine; Neuroscience & Behavior; Molecular Biology & Genetics; Clinical Neurology; Neurosciences; Developmental Biology; Genel Sinirbilim; Moleküler Biyoloji; Nöroloji (klinik); General Neuroscience; Molecular Biology; Neurology (clinical); Boston Carpal Tunnel Questionnaire; Carpal tunnel syndrome; Frequent dropping objects; Long-latency afferent inhibition; Purdue Pegboard Test; Sensorimotor integration; Short-latency afferent inhibition